Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening:Profitabilitas Dan Struktur Modal - Syafrin, Indra (Journal of Science Education and Management Business, 2023)
This study aims to analyze and estimate the effect of corporate governance and capital structure on firm value with financial performance as an intervening variable in manufacturing consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection technique used the Purposive Sampling Method and obtained as many as 24 Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange. The results of this study partially show that the variables of corporate governance, capital structure and financial performance have a significant effect on firm value. Corporate governance and capital structure have a significant effect on financial performance. Financial performance is not able to mediate the relationship between good corporate governance and firm value, financial performance is able to mediate the relationship between capital structure and firm value